Wilson Disease and the COVID-19 pandemic: exploring patients’ mental health and vaccination attitudes in a longitudinal study - Coskun, Ayse K.; Aydin, Adem; Tosun, Sumeyra; To, Uyen; Rubman, Susan; Schilsky, Michael L.; Zimbrean, Paula C. (Frontiers in Psychology, 2024)
Introduction The COVID-19 pandemic significantly impacted the mental health of individuals with chronic conditions such as Wilson’s Disease (WD). This study investigates stress, anxiety, depression, quality of life, cognitive function, vaccination rates, infection rates, and perceptions related to the pandemic and vaccines among WD patients. Methods The study analyzed COVID-19 perceptions and vaccine attitudes of 62 adult WD patients enrolled in the international multisite WD Registry. A subgroup of 33 participants completed a series of mental health scales. The effect of working essentially, income loss, wellness activity initiation, and infection of COVID-19 during the pandemic was observed. Results Results indicate that, overall, the pandemic did not exacerbate anxiety or cognitive function in WD patients but did lead to increased depression among essential workers. Patients experiencing income loss exhibited higher levels of stress and anxiety. Despite these challenges, WD patients showed high vaccination rates and positive attitudes towards vaccines. Discussion The findings underscore the significant impact of the pandemic on the mental health of WD patients.